Illocutionary Acts in President Rodrigo Duterte’s Speech. - Wardana, Muhammad Kiki; Roy, Sumita; Ariska, Juan (Talenta Publisher, 2019)
This research attempts to figure out the speech act of President of The Republic of The Philippines, Rodrigo Duterte, particularly in identifying types of the Illocutionary act and Perlocutionary act in SONA Forum. The researcher is keen to explore duterte’s speech because Duterte is notorious for his unfavorable remarks. Therefore, by investigating his speech through the analysis of his speech act in the selected speech, the researcher will prove whether the speech contains the perlocutionary acts of insulting or not. This research also focuses on utilizing Searle’s theory on Illocutionary acts exemplifies 5 different types of illocutionary acts namely Assertive which is divided into stating, suggesting, boasting, complaining and claiming. Another type is Directives which comprises of ordering, commanding, requesting, advising and recommending. Expressive type comprises thanking, congratulating, pardoning, blaming, praising, and condoling. Commisive type includes promising, vowing, and offering. The last type is Declaration. The researchers use descriptive qualitative method by doing transcription of the speech and meticulously analyze every word.